2019
DOI: 10.1093/rheumatology/kez152
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of switching from rituximab to biosimilar CT-P10 in rheumatoid arthritis: 72-week data from a randomized Phase 3 trial

Abstract: Objective To evaluate the efficacy and safety of CT-P10, a rituximab biosimilar after a single switch, during a multinational, randomized, double-blind Phase 3 trial involving patients with RA. Methods Patients received 48 weeks’ treatment with CT-P10 or United States- or European Union-sourced reference rituximab (US-RTX and EU-RTX, respectively). Patients entering the extension period (weeks 48–72) remained on CT-P10 (CT-P1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 29 publications
2
22
1
1
Order By: Relevance
“…No meaningful differences were observed in safety, immunogenicity or efficacy for patients who switched from the RP in the DB study to FKB327 in the OLE or vice versa. Similar results of treatment safety, efficacy and immunogenicity were reported in the phase 3 EGALITY study of an etanercept biosimilar in patients with chronic plaque psoriasis 14 ; a phase 3 study of a rituximab biosimilar in patients with RA 15 ; and a phase 3 study of an infliximab biosimilar in patients with active Crohn’s disease. 16 Both the EGALITY study and the current study assessed multiple switching between biosimilars and RP treatment; however, the EGALITY study had shorter treatment intervals and follow-up.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…No meaningful differences were observed in safety, immunogenicity or efficacy for patients who switched from the RP in the DB study to FKB327 in the OLE or vice versa. Similar results of treatment safety, efficacy and immunogenicity were reported in the phase 3 EGALITY study of an etanercept biosimilar in patients with chronic plaque psoriasis 14 ; a phase 3 study of a rituximab biosimilar in patients with RA 15 ; and a phase 3 study of an infliximab biosimilar in patients with active Crohn’s disease. 16 Both the EGALITY study and the current study assessed multiple switching between biosimilars and RP treatment; however, the EGALITY study had shorter treatment intervals and follow-up.…”
Section: Discussionsupporting
confidence: 73%
“…14 Studies investigating the rituximab and infliximab biosimilars included a single-switch treatment with follow-up to 72 or 54 weeks, respectively, which was shorter than in the current study. 15 16 Although these studies reported similar outcomes, the current data, based on 6-month switching intervals and 2-year follow-up, provide more robust clinical information on the safety and efficacy of treatment switching in patients with RA.…”
Section: Discussionmentioning
confidence: 69%
“…Other studies have supported the use of anti‐TNF biosimilars. A phase 3 trial investigating a rituximab biosimilar in patients with RA demonstrated that long‐term use of the biosimilar to 72 weeks was well tolerated and effective 21 . In this study, patients who underwent a single switch from the RP to the biosimilar exhibited similar results in terms of efficacy, pharmacodynamics, immunogenicity, and safety.…”
Section: Discussionmentioning
confidence: 58%
“…A phase 3 trial investigating a rituximab biosimilar in patients with RA demonstrated that long-term use of the biosimilar to 72 weeks was well tolerated and effective. 21 In this study, patients who underwent a single switch from the RP to the biosimilar exhibited similar results in terms of efficacy, pharmacodynamics, immunogenicity, and safety. A phase 3 study of an infliximab biosimilar in patients with moderate-to-severe RA demonstrated similar safety, efficacy, and immunogenicity of the biosimilar compared with the RP to 54 weeks.…”
Section: Discussionmentioning
confidence: 60%
“…Several clinical trials assessing CT-P10 in follicular lymphoma and rheumatoid arthritis (26)(27)(28)(29)(30)(31)(32)(33) and a few data concerning the real-world experience (34,35) have been published so far. However, data concerning this compound in pSS are not available.…”
Section: Introductionmentioning
confidence: 99%